Pengaruh metode bernyanyi terhadap peningkatan hasil belajar Bahasa Arab di sekolah Madrasah Ibtidaiyah - Amanah, Amanda Luthfi (Maliki Interdisciplinary Journal, 2024)
This research analyzes the influence of the singing method on Arabic language learning outcomes in Sekolah Madrasah Ibtidaiyah. This method is considered creative and interactive in foreign language learning. The study aims to understand how the singing method affects vocabulary comprehension, grammar understanding, speaking skills, and student motivation in learning the Arabic language. Data were collected through observations and interviews with Arabic language teachers who employed the singing method. The research findings indicate that the use of the singing method has a positive impact on vocabulary comprehension, grammar understanding, and speaking skills of students. Additionally, student motivation and engagement also increase. These findings demonstrate that the singing method can effectively enhance Arabic language learning outcomes in madrasahs. However, integration with other learning approaches remains important. This study offers new insights into the potential of the singing method in Arabic language education.